2022
DOI: 10.18596/jotcsa.1019969
|View full text |Cite
|
Sign up to set email alerts
|

Ricinus Communis Seed oils as a Source of Biodiesel; A Renewable Form of Future Energy

Abstract: Diminishing supply and environmental pollution of fossil fuels are the vital factors leading to the search of alternative sources of energy like biodiesel. Biodiesel is one of the eco-friendly substitutes of energy which is mainly utilized in diesel engines. Ricinus communis (castor plant), which belongs to the family Euphorbiaceae yields an oil rich beans and plays important role in the production of biodiesel. Recently, the demand of castor oil and its products has been raised in the world market due to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…These variations in the yield of essential and seed oils may be related to variations in soil types, weather conditions, and other growth conditions. The oil yield of R. communis obtained in this study was better than that of Gebrehiwot and Zelelew [33]. They reported that the plant seeds collected from farmland around Abiy Adi, central province, 95 km from the capital of Tigray, Ethiopia, had an oil yield of 9.25%.…”
Section: Essential and Seed Oil Yieldsmentioning
confidence: 49%
See 1 more Smart Citation
“…These variations in the yield of essential and seed oils may be related to variations in soil types, weather conditions, and other growth conditions. The oil yield of R. communis obtained in this study was better than that of Gebrehiwot and Zelelew [33]. They reported that the plant seeds collected from farmland around Abiy Adi, central province, 95 km from the capital of Tigray, Ethiopia, had an oil yield of 9.25%.…”
Section: Essential and Seed Oil Yieldsmentioning
confidence: 49%
“…Finally, the seed oils from each extraction beaker, containing a small amount of extraction solvent, were combined and further concentrated using a rotary evaporator. The amount of oil recovered and its percentage in the original sample were calculated as follows [18,33] Oil content (%) = Mass of oil extracted (g) Sample weight (g) × 100…”
Section: Extraction Of Seed Oilmentioning
confidence: 99%
“…Castor seeds are mainly composed of four parts: embryo, endosperm (with oil), coat and caruncle (Severino et al, 2021). The castor seeds are rich in oil, about 30%–50% (Srinivasan et al, 2021), and the oil is becoming an important bio‐diesel production composition (Gebrehiwot & Zelelew, 2022). The castor oil extraction methods include mechanical, chemical, and enzymatic.…”
Section: Introductionmentioning
confidence: 99%
“…The castor seeds are rich in oil, about 30%-50% (Srinivasan et al, 2021), and the oil is becoming an important bio-diesel production composition (Gebrehiwot & Zelelew, 2022). The castor oil extraction methods include mechanical, chemical, and enzymatic.…”
mentioning
confidence: 99%